2011
DOI: 10.1111/j.1365-2842.2011.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

The shortened dental arch revisited: from evidence to recommendations by the use of the GRADE approach

Abstract: Clinicians must frequently decide whether or not to treat patients with loss of posterior teeth, a condition called the shortened dental arch (SDA). Although many studies have been reported, there are no clear recommendations for the management of SDA cases. In this work, therefore, an innovative system, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach, was used to grade the evidence and strength of recommendations for clinical intervention. An extensive literature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…This entails directing the limited resources towards that part of the dentition that can be successfully preserved and in the most cost-effective manner, rather than on the remaining molar teeth that often have a poorer prognosis [5], [7], [31][58]. The minimum number of teeth or shortness of the arch will also depend on the periodontal condition of the remaining teeth, the age of the patient, occlusal activity, food types and adaptive capacity of the patients’ temporomandibular joints [3], [7], [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This entails directing the limited resources towards that part of the dentition that can be successfully preserved and in the most cost-effective manner, rather than on the remaining molar teeth that often have a poorer prognosis [5], [7], [31][58]. The minimum number of teeth or shortness of the arch will also depend on the periodontal condition of the remaining teeth, the age of the patient, occlusal activity, food types and adaptive capacity of the patients’ temporomandibular joints [3], [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other associated benefits of the SDA have been enumerated by several researchers [5]–[8], [10]–[20], [31][58]. A number of studies have been conducted in Tanzania where the evidence obtained was used to advise the government, medical and dental personnel to include the SDA concept within the prosthodontic management protocols for the country [12], [16], [50]–[52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Multiple iterations of the SDA exist based on the number and distribution of occluding pairs of posterior teeth. 5 The aim of this systematic review was to summarise the impact of RPD provision on objective measures of masticatory function in SDA and extreme SDA patients (eSDA). The review question, inclusion criteria and search strategy were clearly defined and a reasonable publication-date restriction was applied.…”
mentioning
confidence: 99%
“…Because GRADE takes into account variables other than quality of evidence, it may be a good basis for more transparent and systematic decision making. 14,15 In summary, this work has revealed that, currently, the overall quality of evidence in dentistry is low. Researchers, clinicians, and all involved with dental treatment should combine efforts to improve the quality of evidence in the several disciplines of dentistry.…”
Section: Discussionmentioning
confidence: 93%